2018
DOI: 10.1007/s00198-018-4395-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isolated vitamin D supplementation on bone turnover markers in younger postmenopausal women: a randomized, double-blind, placebo-controlled trial

Abstract: In younger postmenopausal women with VD deficiency, isolated supplementation with 1000 IU of vitamin D3 for 9 months is associated with a reduction in bone turnover markers. However, any between-group differences was not observed in bone turnover markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 40 publications
2
35
0
2
Order By: Relevance
“…However, the relationship between vitamin D concentration and bone resorption or formation biomarkers is still inconclusive because of different study group ages, ethnicities, or countries in various latitudes. A randomized, double-blind, placebo-controlled trial in postmenopausal women showed that supplementation with 1000 IU of vitamin D 3 daily can significantly increase both serum CTX and P1NP levels, which means administration of vitamin D can restore the decrease in bone resorption and formation [103]. Additionally, the PTH level significantly decreases together with an elevated vitamin D level after vitamin D is given [103].…”
Section: The Association Of Uric Acid and Bone Health In Epidemiolmentioning
confidence: 99%
“…However, the relationship between vitamin D concentration and bone resorption or formation biomarkers is still inconclusive because of different study group ages, ethnicities, or countries in various latitudes. A randomized, double-blind, placebo-controlled trial in postmenopausal women showed that supplementation with 1000 IU of vitamin D 3 daily can significantly increase both serum CTX and P1NP levels, which means administration of vitamin D can restore the decrease in bone resorption and formation [103]. Additionally, the PTH level significantly decreases together with an elevated vitamin D level after vitamin D is given [103].…”
Section: The Association Of Uric Acid and Bone Health In Epidemiolmentioning
confidence: 99%
“…Observational studies report increased bone resorption with vitamin D deficiency [35, 36]. Despite observations of increased bone turnover, RCT’s assessing the effect of vitamin D supplementation on markers of bone turnover have shown inconsistent results [25, 26, 3739].…”
Section: Discussionmentioning
confidence: 99%
“…However, in subjects whose 25(OH)D concentration exceeded 30 ng/ml, an increase of CTX levels was observed [21]. Conversely, it has been demonstrated that improved vitamin D status in younger postmenopausal women leads to a signi cant reduction in serum CTX and PINP levels [22]. The ndings of the current study are in agreement with the latter study, in that we observed that in both EG and PAM groups, concentration of 25(OH)D below the median value of 22.50 ng/ml was associated with higher CTX levels at baseline.…”
Section: Response To Want and Vitamin Dmentioning
confidence: 99%